New synonyms of Pohlia wahlenbergii (Bryaceae) in the austral regions - Ochyra Ryszard (2011)
Taxonomic Additions and Changes: Pohlia wahlenbergii (F.Weber & D.Mohr) A.L.Andrews (Bryum aptychoides Müll.Hal., syn. nov.; B. alticaule Müll.Hal. var. robustius Müll.Hal., syn. nov.; Mniobryum alticaule (Müll.Hal.) Broth. var. crassinerve Broth.,syn. nov.; B. austroalbicans Müll.Hal., B. aptychoides Müll.Hal., B. alticaule Müll.Hal., Mniobryum alticaule (Müll.Hal.) Broth. var. crassinerve Broth. = new lectotypes).